Improving Mathematics Learning Outcomes on the Concept of Number Multiplication with a Realistic Mathematics Education Approach at SD Negeri Cijeruk I Mekar Baru - Faizah; Atikah (MANDAILING GLOBAL EDUKASIA, 2024)
The Realistic Mathematics Education approach is one of the ways to improve student learning outcomes in Mathematics subjects, because mathematics is very closely related to everyday life. In this research, the Classroom Action Research method is used which consists of four stages, namely, the planning stage, the implementation stage, the action stage, the observation and reflection stage. The four stages cover two cycles. While the data collection instrument in this research includes observation guidelines based on learning levels, learning outcomes tests to determine the improvement of student learning outcomes after the learning process given by the teacher using the Realistic Mathematics Education Approach, interviews to find out the problems that occur in schools and documentation. The data analysis technique used in this method is the average value of the class and the percentage of completion. Thus it can be concluded that using the Realistic Mathematics Education approach can improve the learning outcomes and activities of students in class IV of the Negeri Cijeruk Satu Subdistrict, Mekar Baru Subdistrict, Tangerang Regency. on the concept of multiplication of numbers, the material operation of multiplication of one-digit numbers with two-digit and three-digit numbers and multiplication operations in accordance with the nature of multiplication. This can be seen from the average value of the precycle before using the Realistic Mathematics Education Approach of 43.5 with a completion percentage of 24%, cycle I after using the Realistic Mathematics Education Approach increased by 64.4 with a completion percentage of 60% and cycle II increased by 83.2 with a completion percentage of 96%. As for student learning activities in cycle I reached 20%, and in cycle II reached 96%.